Biomechanics-based Gradient Nano-surface Implants Screening and Its Adoption in Dental Implant Repair - Wei Niu; Xin Wang; Tao Li; Bo Feng (SLAS Technology)
Background: this study aimed to screen the micro/nano surface of pure titanium implant gradient for performance analysis, and to explore its role in dental implant repair. Methods: after treatment with different concentrations of hydrofluoric acid and varying etching times, titanium plates with micro/nano gradient surfaces were selected and divided into four groups: polished, b, c, and d. The microscopic morphology of the titanium surfaces was observed, and the contact angle was measured. One implant was inserted into the femoral metaphysis on both sides of 28 SD rats. Histological sections were analyzed, and the maximum pull-out force was measured. Results: the new bone trabeculae on the surfaces of groups b, c, and d were wider as against polished group. The surface morphology of the titanium disks etched with 1.2 % hydrofluoric acid for 15 min (group d) was more uniform, the diameter of micropores was the largest, and the contact angle was the smallest (12.1 ± 1.17°). The new bone structure on the surface of implant screws in group d was slightly higher as against groups b and c. The bone-to-implant contact (BIC) and the maximum pullout force in groups b (33.25±2.57 %, 58.52±4.03 N), c (35.16±2.35 %, 59.43±3.97 N), d (40.93±2.71 %, 68.22±4.36 N) were higher as against polished group (22.41±2.86 %, 30.12±4.71 N) (P < 0.05). Three months after implantation, the bone fusion rate in the other three groups was significantly higher than that in the polishing group, with group d showing higher rates compared to groups b and c (P < 0.05). Conclusion: the gradient micro/nano surface was constructed by hydrofluoric acid. The osseointegration of hydrofluoric acid etching implant surface and implant was clearly better as against polished group.